Negative air ions and lucidity induction: additional data - Gackenbach, Jayne; Adler, Thomas; LaBerge, Stephen (My University, 1983)
It has been reported that using a negative ion generator in ones bedrooms may be detrimental to falling asleep. The general influence of negative air ions on the brain may be a lower arousal threshold. Too much arousal keeps us awake; but by controlling the negative ion concentration individuals may find that they are able to sleep while retaining a tendency for heightened arousal in dreams. In this way negative ions may be conducive to lucidity. Adler reports that the frequent appearance of rain in his dreams in an ionized environment may also express this arousal effect. Sometimes this “rain” assumes bizarre forms: emeralds falling out of the sky, thousands of birds descending, but usually it is ordinary rain. Falling water and rainstorms are the natural source of negative air ions.
Keywords: dreams; negative air ions; lucidity induction